PENGARUH BI RATE, OPERATIONAL EFFICIENCY RATIO, CAPITAL ADEQUACY RATIO, NET INTEREST MARGIN, DAN NON PERFORMING LOAN PADA RENTABILITAS - Setiawan, Andrik Aprilyanto; Supadmi, Ni Luh (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2019)
Banking rentability is banking capabilities by gaining profits in relation to sales, total assets, and own capital. This study aims to examine the influence of external and internal factors, namely the BI Rate, Operational Efficiancy Ratio, Capital Adequacy Ratio, Net Interest Margin, and Non Performing Loans on Rentability of Persero, Tbk. This research was conducted at all banks included in the Group of Persero, Tbk., And listed on the IDX for the period 2015 - 2018. The number of samples taken was saturated sampling, amounting to 4 samples. Data collection in this research is done by tracing monthly and annual reports. Data analysis was performed using multiple regression analysis. The results of this study indicate that the BI Rate and C apital Adequacy Ratio have no effect on rentability. This research also proves that Operational Efficiency Ratio , Net Interest Margin, and N Non Performing Loan significantly influence Rentability.